Pemberdayaan Lahan Pekarangan Untuk Ketahanan Pangan Masyarakat Urban Sawah Lebar Bengkulu - Aprinata, Pirga Ulan; Perdiansa, Jeri; Setiawan, Alex; Oktavianti, Selvi; Akbar, Raka Fahri; Fitria, Yenni; Nur’aini, Hesti; Susena, Karona Cahya (Universitas Dehasen Bengkulu, 2026)
Unmanaged home yards are common problem in urban Indonesia, including RT 04 Sawah Lebar Village, Bengkulu. Thematic Community Service Program of Dehasen University implemented food crop cultivation in home yards to improve food security and economic empowerment. Methods include Focus Group Discussion, cultivation training, technical assistance, and regular monitoring. Results show participation of 40 households with 85% cultivation success rate. Program successfully increased community knowledge about urban farming and produced productive crops.